2010
DOI: 10.1108/09574091011042160
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the importance of attributes in logistics research

Abstract: PurposeTraditional methods of capturing and determining logistics attribute importance have serious research limitations. The purpose of this paper is to introduce maximum difference (MD) scaling as a new research methodology that will improve validity in measuring logistics attribute importance, overcoming many of the limitations associated with traditional methods. In addition, this new research method will allow logistics researchers to identify meaningful need‐based segments, an important goal of logistics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Hierarchical Bayes within Sawtooth Software (7.0) was used to analyze the MD data. Best practice in choice modeling suggests that Hierarchical Bayes is the "gold standard" of excellence (Garver, Williams, and LeMay 2010 ). The results from the Hierarchical Bayes analysis were rescaled so that the preference scores assigned to each transit time and rate would sum to 100 points, with higher scores refl ecting greater preference for the transit time and rate.…”
Section: Results: Transit Time and Rate Preferencesmentioning
confidence: 99%
“…Hierarchical Bayes within Sawtooth Software (7.0) was used to analyze the MD data. Best practice in choice modeling suggests that Hierarchical Bayes is the "gold standard" of excellence (Garver, Williams, and LeMay 2010 ). The results from the Hierarchical Bayes analysis were rescaled so that the preference scores assigned to each transit time and rate would sum to 100 points, with higher scores refl ecting greater preference for the transit time and rate.…”
Section: Results: Transit Time and Rate Preferencesmentioning
confidence: 99%
“…Research conducted among Czech customers showed that the most important factors in assessing the quality of services in road transport of cargo are: no damage in packaging, keeping delivery dates, no damage to transported goods, no accidents in transport processes (Koniecny, Stetinova, 2006). From the practice point of view, knowledge about quality attributes determines the direction of development and investments and determines the success rate of carriers decision making processes (Garver et al, 2010). The faster the operators' response to the specific customer requirements, the higher they will be assessed.…”
Section: Methodology and Theorymentioning
confidence: 99%
“…Although contextually different, the study served as methodological guidance for the BWS analysis as presented in this article. Additionally, we followed the BWS steps as proposed by [86]. Accordingly, the first step comprised the setting of the study context followed by the identification of attributes.…”
Section: Best-worst Scaling Surveymentioning
confidence: 99%